A Note on Solitary Wave Solutions of the Nonlinear Generalized Camassa-Holm Equation. (6th February 2013) - Zhang, Lei; Wang, Xing Tao
Abstract : We give a simple method for applying ordinary differential equation to solve the nonlinear generalized Camassa-Holm equation u t + 2 k u x − u x x t + a u m u x − 2 u x u x x + u u x x x = 0 . Furthermore we give a new ansätz. In the cases where m = 1, 2, 3, the numerical simulations demonstrate the results.